1990
DOI: 10.1007/bf00752771
|View full text |Cite
|
Sign up to set email alerts
|

Serving the chronic mentally ill in state and community hospitals

Abstract: Acute psychiatric admissions to three state and three community hospitals from the same geographic areas were examined in terms of patient characteristics, services, and costs. Overall, patients in state hospitals were more likely than patients in community hospitals to be admitted involuntarily, to have bizarre or assaultive behaviors as a precipitating cause of admission, to have recent community mental health involvement, to be referred by family or friends, to be living in dependent care at admission, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1990
1990
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…Systematic differences in either overall severity or in length of stay, or both, according to legal status, could go some way to accounting for the public-private differences observed. It is reasonable to expect that involuntary patients will have more severe problems than their voluntary counterparts [14]. Unpublished data from the Victorian field trial of the HoNOS in the public sector showed that the mean total score (computed on just the 11 items common to HoNOS versions 3 and 4) was 13.2 for 64 voluntary inpatients and 14.6 for 172 involuntary inpatients.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic differences in either overall severity or in length of stay, or both, according to legal status, could go some way to accounting for the public-private differences observed. It is reasonable to expect that involuntary patients will have more severe problems than their voluntary counterparts [14]. Unpublished data from the Victorian field trial of the HoNOS in the public sector showed that the mean total score (computed on just the 11 items common to HoNOS versions 3 and 4) was 13.2 for 64 voluntary inpatients and 14.6 for 172 involuntary inpatients.…”
Section: Discussionmentioning
confidence: 99%
“…Em uma pesquisa (6) comparando as características de indivíduos internados em hospitais psiquiátricos tradicionais com os de instituições comunitárias (hospitais gerais, hospitais dia), foi concluído que não havia diferenças significativas entre estes grupos no que se refere a internações anteriores e comportamento dentro da instituição. No entanto, os admitidos nos hospitais tradicionais o eram, mais freqüentemente que o outro grupo, de forma involuntária; tinham indicações para serem internados que variavam de pressões familiares, de amigos, ou mesmo policial, por comportamento bizarro ou ameaçador; e viviam sob a dependência de cuidados básicos dos outros (família, sociedade).…”
Section: Introductionunclassified